Theoretical Models of Taxation of Holding Companies in Member States of the European Union - Gajewski, Dominik J. (Warsaw Forum of Economic Sociology, 2017)
Currently, a holding company is one of the most popular form of organisation in the globalized Europe. The tax situation of such entities is a significant condition determining cross-border operations. Therefore, the objective of this article is to analyse the theories of taxation of holding companies conducting business activity on the territory of the EU. Analysis shows how great a variety of models (theories) of taxation, which are available in various EU Member States, a holding company may use. Individual tax theories are characterised by particular constructions that have both advantages and disadvantages.